Features of calcium metabolism during pregnancy depending on body saturation of vitamin D - E S Shelepova; I E Zazerskaya; E L Chazova; L V Kuznetsova; N Yu Yakovleva; E Yu Vasileva (IP Berlin A.V., 2016)
Objective. The objective of this research was to estimate influence of vitamin D saturation on calcium metabolism in pregnancy. Materials and methods. Cohort retrospective and prospective study. 110 pregnant women (mean age 29,64±2,3 years) at 30-38 weeks of pregnancy were examined. Investigation time lasted from September 2013 to June 2014. All patients had blood sampling done with the following determination of the levels of 25-hydroxycalciferol, calcium, parathyroid hormone. All patients lived in Saint Petersburg and Leningrad region. From 12 gestational week all patients were using a multivitamin complex, which contained 400 IU of vitamin D. Results. 110 pregnant were analyzed. Among all examined pregnant women the normal blood serum level of 25-OH-D was in 49 (44,5%) pregnant, 25-OH-D insufficiency - in 22 (20%) patients, 25-OH-D deficiency - in 39 (35,5%) pregnant. Calcium level in blood serum in pregnant with normal vitamin D saturation was 2,32±0,06 mmol/L, with insufficiency - 2,17±0,03 mmol/L, with vitamin D deficiency - 2,08±0,02 mmol/L Parathyroid hormone levels in blood serum in pregnant with normal vitamin D saturation was 23,63±1,9 pg/ml, with vitamin D deficiency - 31,±2,3 pg/ml. Conclusion. The increase of parathyroid hormone in blood serum occurs during the insufficient saturation of vitamin D in pregnant women. In pregnant with vitamin D deficiency and insufficiency relative hypocalcemia occurs. Received data confirm correlation between body saturation of vitamin D and calcium metabolism during pregnancy.